A reversed-phase high performance liquid chromatography approach for analysis of 5-Fluorouracil - Soha Azadi; Amir Azadi; Hajar Ashrafi; Soliman Mohammadi-Samani (Shiraz University of Medical Sciences, 2017)
A reproducible, sensitive, accurate and selective high performance liquid chromatographic (HPLC) method with ultraviolet absorbance detection has been developed and validated to quantitate 5-Fluorouracil (5-FU), an antimetabolite chemotherapeutic agent used in treatment of colorectal cancer as a drug of choice. Chromatographic separations were performed on a C18 column (Eurosphar 100-5, 150 mm × 4.6 mm) as the reversed stationary phase, eluted with a mobile phase composed of deionized water and methanol (95:5) with the flow rate of 1.0 mL/min. The UV wavelength was set at 261nm. The method produced linear responses throughout 5-fluorouracil range of 25-500 ng/ml with a correlation coefficient of 0.998. A limit of quantitation (LOQ) was established at 25 ng/ml. The within-day and between-day precision and accuracy were both in acceptable ranges. The outcomes of these tests indicate a proper separation efficacy as well as accuracy and sensivity of method which is a potential tool in many pharmaceutical studies such as drug delivery of this anti-cancer agent.